EFFICACY AND ENTERTAINMENT IN MARTIAL ARTS STUDIES anthropological perspectives - Farrer, Douglas S. (Martial Arts Studies, 2015)
Martial anthropology offers a nomadological approach to Martial Arts Studies featuring Southern Praying Mantis, Hung Sing Choy Li Fut, Yapese stick dance, Chin Woo, Brazilian jiu-jitsu, and seni silat to address the infinity loop model in the anthropology of performance/performance studies which binds together efficacy and entertainment, ritual and theatre, social and aesthetic drama, concealment and revelation. The infinity loop model assumes a positive feedback loop where efficacy flows into entertainment and vice versa. The problem addressed here is what occurs when efficacy and entertainment collide? Misframing, captivation, occulturation, and false connections are related as they emerged in anthropological fieldwork settings from research into martial arts conducted since 2001, where confounded variables may result in new beliefs in the restoration of behaviour.
Created from Fastlane, Scopus look-up
Keywords: Brazilian jiu-jitsu; Chinese martial arts; Efficacy; entertainment; nomadology; performance; seni silat